Contrast‐enhanced μCT of the intervertebral disc: A comparison of anionic and cationic contrast agents for biochemical and morphological characterization. Issue 5 (22nd July 2016) - Newton, Michael D.; Hartner, Samantha E.; Timmons, Shannon; Delaney, Nathan D.; Pirrone, Michael G.; Baker, Kevin C.; Maerz, Tristan
ABSTRACT: The objective of this study was to quantify and compare the contrast‐enhancing properties of the anionic contrast agent ioxaglate/Hexabrix, and cationic contrast agent CA 4+ for biochemical and morphological characterization of the intervertebral disc (IVD) via μCT. Optimal contrast agent concentrations were determined by incubating rat lumbar IVDs in dilutions of Hexabrix‐320 (20%, 30%, 40%, and 50%) and CA 4+ (10, 20, 30, and 40 mg I/ml). μCT imaging was performed at 70 kVp, 114 μA, and 250 ms integration time, 12 μm voxel size. The kinetics of contrast enhancement were quantified with cumulative incubations for 0.5, 1, 2, 12, 16, 20, and 24 h using both agents. Agreement in morphological quantification was assessed via serial scans of the same IVDs. Correlation of attenuation to glycosaminoglycan (GAG) content was determined by enzymatic digestion of IVDs, subsequent μCT imaging, and GAG quantification via dimethylmethylene blue assay. Forty percent Hexabrix and 30 mg I/ml CA 4+ were chosen as optimal concentrations. Hexabrix enabled greater delineation of the IVD from surrounding tissues, and CA 4+ had the lowest uptake in surrounding soft tissue. Twenty‐four hour incubation was sufficient for >99% equilibration of both agents. A high level of agreement was observed in the quantification of IVD volume (ICC = 0.951, r = 0.997) and height (ICC = 0.947, r = 0.991). Both agents exhibited strong linear correlations between μCT attenuation and GAG content (Hexabrix: r = −0.940; CA 4+ : r = 0.887). Both agents enable biochemical and morphological quantification of the IVD via contrast‐enhanced μCT and are effective tools for preclinical characterization. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1067–1075, 2017. Abstract : Both the anionic contrast agent Hexabrix and the cationic contrast agent CA 4+ enable biochemical and morphologic quantification of the intervertebral disc (IVD) via contrast‐enhanced µCT. Both agents exhibited strong linear correlations between µCT attenuation and glycosaminoglycan (GAG) content (Hexabrix: r = −0.940; CA 4+ : r = 0.887) following enzyme‐mediated digestion. In morphological analysis, a high level of agreement was observed in the quantification of IVD volume (ICC = 0.951, r = 0.997) and height (ICC = 0.947, r = 0.991).